Bionic hierarchy growth method for optimal design of dendritic heat transfer structure. Issue 7 (2nd July 2020) - Xiong, Min; Ding, Xiaohong; Ji, Yidong
ABSTRACT: To design an effective and easy-to-manufacture conductive heat transfer structure, a bionic hierarchy growth method inspired by a natural branch system is suggested. The heat transfer structure is assembled by heat channels which are determined by width, start point and end point. Hierarchy growth consists of successive growth of principal channel and lateral channel. Specifically, the space colonization algorithm with temperature information (SCATI) is applied to the growth of the principal channels, and the law of minimal thermal resistance is applied to control the growth of the lateral channels. The superiority of the suggested method is demonstrated by three typical design problems. In addition, design parameters including the number of principal channels and the bifurcation exponent in Murray's law are discussed, and the results prove the reasonability of the parameter selection based on natural branch systems. Finally, the thermal performance comparison between the structure designed by constructal theory and a dendritic heat transfer structure shows experimentally the effectiveness of the suggested method.